Study of critical micelle concentration of cetyltrimethylammonium bromide (CTAB) in pure water in presence and absence of magnesium sulphate and sodium sulphae by measuring conductivity meter - Bhattarai, Ajaya; Shrivastav, Ghanashyam; Adhikari, Chom Nath (BIBECHANA, 2014)
The precise measurement of specific conductivity of cetyltrimethylammonium bromide (CTAB) in distilled water at room temperature was reported and also the specific conductivity of cetyltrimethylammonium bromide was measured in the presence of magnesium sulphate and sodium sulphate using a conductivity meter. The critical micelle concentration of three systems was calculated. The comparison of cmc among them was also performed. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10390 BIBECHANA 11(1) (2014) 123-127